Pedagogic translation: Experiments and exercises to do in class - Figueira de Souza Corrêa, Elisa (Universidade Estadual Paulista, 2017)
This paper reports several experiments and proposals of exercises that were done in non-native language classrooms. The objective is to justify and promote pedagogic translation use in non-native language teaching. By these examples, it is clear that translation helps to enhance student’s language awareness and to develop a certain translation ability (i.e. a fifth skill) – which is essential in life beyond classroom.